Analisa Tingkat Kepuasan Masyarakat Terhadap Kualitas Siaran TV Digital - Adela, Adra; Santoso, Puji (Universitas Muhammadiyah Sumatera Utara, 2024)
Television production is a broadcasting process that produces audiovisual material containing program content, produced in the production department and broadcast by a group of professionals in their respective fields, working professionally based on television criteria to be aired through television media targeted at the general public. This study aims to analyze the level of public satisfaction with the quality of digital TV broadcasts. The time the author used for this research was carried out in February 2024 in the Karang Berombak Village, Environment X, Alley XVIII, Medan. The data collection techniques used by the author in this study were interviews and observations. The data analysis carried out in this study used the Uses and Gratifications Theory. The result of this research is that digital TV broadcast users provide a personal integrative effect. Digital TV content can influence how individuals interact with others and understand societal perspectives.